QUALITATIVE RESEARCH IN REGIONAL GEOGRAPHY. A METHODOLOGICAL APPROACH - ILOVAN, Oana-Ramona; DOROFTEI, Iulia (2017)
The aim of this book is to encourage Romanian students andgeographers to take an interest in qualitative research. Itanswers a need in the Romanian university geographicalsystem: that of exploring the role of qualitative researchmethods and their usefulness and relevance both for researchand for university students’ professional training. Given thefact that, for a very long time, Romanian geographers used thedescriptive method and the quantitative ones, very often nottrusting the qualitative methods and the results obtained withsuch “subjective” methodology, a pro domo book like thisvolume is necessary.